Design and implementation of adaptive and synchronous test function of chip sample verification platform - Xu Jinglin; Wang Dong; Wei Bin; Wang Yun; Dou Zhijun; Cheng Song (Dianzi Jishu Yingyong, 2023)
At present, in chip design companies, sample verification is carried out for mass production chips. Most of the traditional sample verification methods design corresponding test equipment based on the characteristics of the chip, and then test the chip samples one by one through the test fixture. Different chips will design different test equipment. In this paper, an adaptive and synchronous test sample verification platform scheme is proposed, which can not only test multiple chips at the same time, but also test chips with different interfaces. It can not only test the reliability experiment, but also test other functions, which greatly saves the maintenance cost of test equipment and improves the test efficiency.